Local Government Authority in Managing Non-State-Owned Forest Areas to Reduce Deforestation - Redin Redin; Charis Kristotes Jordan (Faculty of Law, University of Merdeka Malang, 2023)
Analyze the authority of local governments in maintaining forest cover in forest areas that are not owned by the state or APL as life support from deforestation due to forest conversion into business areas. Looking at the considerations for determining the 10 areas with the Decree of the Sintang Regent in the APL, shows that APL has an essential function as a community environment. Therefore, forests and biodiversity in APL must be managed by prioritizing the function of environmental protection. This research is normative, with data collection techniques carried out by library researchers. The results of the study show that the Sintang Regency Government is given the authority to manage APL in its administrative area based on the Decree of the Minister of Forestry Number SK.733/Menhut-II/2014 concerning Forest Areas and Marine Conservation in West Kalimantan Province. Through Government Regulation Number 23 of 2021, the government encourages regional governments according to their authority to protect forest cover in APL that do not yet have business permits to fulfill the carrying capacity and environmental capacity to reduce the rate of deforestation in non-state-owned forest areas.How to cite item: Redin, and Charis Kristotes Jordan. â€œLocal Government Authority in Managing Non-State-Owned Forest Areas to Reduce Deforestation.â€ Jurnal Cakrawala Hukum. 14 no. 1 (2023): 36-45. DOI: 10.26905/idjch.v14i1.9101.